Chirality-selective Raman scattering of the D mode in carbon nanotubes - Maultzsch, Janina; et al. (Physical Review B, 2001)
We show that D-mode Raman scattering in single-walled carbon nanotubes is due to a double-resonant Raman process. The unusual shift of the D-mode frequency with excitation energy is even expected for a single nanotube. The magnitude of the shift and the D-mode frequency depend strongly on the tube's diameter and chirality. Only tubes with (n(1)-n(2))/3n integer contribute to the D-mode spectrum because of the particular electronic structure of carbon nanotubes.